Rapid prototyping technology: the next keystone for small and medium ceramic industry - Ab. Aziz Shuaib; Olalere, Folasayo Enoch; Khairul Azhar bin Mat Daud (2015)
Many manufacturers believe building of physical prototypes is a bottleneck that slows down production process and increase production cost. However, since the quest for reality ends up with making real objects, physical prototypes cannot be out-rightly eliminated in product development process. With the advent of rapid prototyping technology (3D printer), manufacturing is now possible at any scale, from units of one to millions, large or small batches. Thus, rapid prototyping is seen as a possible technology for enhancing product development process; especially in small and medium industries that relies on manual production techniques. Hence, this paper investigates the viability of rapid prototyping technology in small and medium industries. With particular reference to ceramic industry, the paper demonstrates how the contemporary technology (Rapid prototyping) can be harmoniously merged with conventional techniques, so as to enhance product quality and reduce development time and cost.